STRATEGI PERUSAHAAN, BUDAYA PERUSAHAAN DAN KOMPENSASI TERHADAP KINERJA - Maesaroh Maesaroh (Universitas La Tansa Mashiro, 2018)
The purpose of this research was to examine empirically the effect between corporate strategy, corporate culture and compensation on job performance among the employees at Prima Rezeki Pertiwi Company in Banten. The subjects of this research were 60 employees selected as samples by using boring sampling technique taken from the overall population of 60 employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ performance was positively affected by the corporate strategy, corporate culture and compensation at Prima Rezeki Pertiwi Company in Banten, and the compensation was positively affected by the corporate strategy and the corporate culture. The findings suggest that the variation of the job performance of the employees might have been affected by the corporate strategy, corporate culture and the compensation.